Emerging Psychotropic Drug for the Treatment of Trigeminal Pain: Salvinorin A - Geovanna Nallely Quiñonez-Bastidas; Lucia Elhy Grijalva-Contreras; Selene Isabel Patiño-Camacho; Andrés Navarrete (Pharmaceuticals)
Trigeminal neuralgia (TN) is chronic pain caused by damage to the somatosensorial system on the trigeminal nerve or its branches, which involves peripheral and central dysfunction pain pathways. Trigeminal pain triggers disruptive pain in regions of the face, including within and around the mouth. Besides clinical experiences, translating the language of suffering into scientific terminology presents substantial challenges. Due to the complex and multifactorial pathophysiology underlying trigeminal pain, elucidating its social impact presents significant difficulties. Carbamazepine and oxcarbazepine are first-line treatments for TN, achieving approximately 50% pain reduction in 60–70% of treated patients. However, their efficacy is often limited by common side effects, such as dizziness, vertigo, nausea, seizures, and cognitive symptoms. In some cases, patients experience severe side effects, including myelosuppression, hyponatremia, hormonal imbalances, liver toxicity, suicidal ideation, teratogenicity, and other adverse reactions. Given these clinical limitations, the search for new painkiller candidates continues. Hence, we focused this review on salvinorin A (SalA), a natural agonist of κ-opioid receptors (KORs), which demonstrated anti-nociceptive, anti-inflammatory, and anti-neuropathic properties in various experimental models of the spinal sensory system. Furthermore, preclinical evidence indicates that SalA does not induce dependence and demonstrates a favorable toxicological and safety profile in comparison with currently marketed opioid drugs. We propose Salvinorin A as a promising candidate for treating trigeminal neuralgia, offering the potential for reduced adverse effects.